2011
DOI: 10.1140/epjst/e2011-01360-0
|View full text |Cite
|
Sign up to set email alerts
|

Liquid entrainment by gas flow along the interface of a liquid bridge

Abstract: Abstract. We report the results of numerical and experimental studies of two-phase flows in an annulus. The geometry corresponds to a cylindrical liquid column co-axially placed into an outer cylinder with solid walls. Gas enters into the annular duct and entrains the initially quiescent liquid. The internal column consists of solid rods at the bottom and top, while the central part is a liquid bridge from a viscous liquid and kept in its position by surface tension. Silicone oil 5cSt was used as a test liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Furthermore, when the dynamic viscosity of the liquid is more than 100 times that of the gas, the strength of the vortex scales linearly with the gas flow Reynolds number , based on the mean gas velocity and twice the width of the air gap. Similar results were reported by Gaponenko, Miadlun & Shevtsova (2011 b ). Gaponenko et al.…”
Section: Introductionsupporting
confidence: 92%
“…Furthermore, when the dynamic viscosity of the liquid is more than 100 times that of the gas, the strength of the vortex scales linearly with the gas flow Reynolds number , based on the mean gas velocity and twice the width of the air gap. Similar results were reported by Gaponenko, Miadlun & Shevtsova (2011 b ). Gaponenko et al.…”
Section: Introductionsupporting
confidence: 92%
“…In physical experiments, we use the ideal isothermal model to improve the quality of silicon crystal. Deformation of an isothermal interface is extremely related to a co-axial gas flow when enter from the bottom to the top, which was discussed by Gaponenko [1,2] , and they reported that the linear velocity of gas almost determined the free surface deformation. The tendency that surface deformation grows with the volume ratio V quasi-linearly was predicted by Gaponenko [3] .…”
Section: Introductionmentioning
confidence: 99%